FIKIH PRO PLURALISME SEBAGAI SOLUSI MEMBANGUN SINERGI AGAMA-AGAMA - Askhabul Kirom (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2017)
There is a gap between classical Jurisprudence and the reality of humanity. The classical Jurisprudence is considered incapable of answering the challenges of the times that have changed drastically along with the spread of Islam to various parts of the world. A pluralistic society entity consisting of nations, religions and cultures has made classical Jurisprudence adaptable to contemporary laws among believers. The problem of jihad for example, can no longer be understood only as a war by taking up arms. The jihad terminology has been expanded in a contextual definition in which Muslims live. Similarly, minority-majority issues, ethnic and human rights issues, and issues of pluralism and multiculturalism practices. This article takes the form of a discourse on the new building of fiqh that is pro-pluralism in religious social relations among the adherents of religion. Data analysis in this research is done in descriptive-analysis, that is exposing data about pro fiery of pluralism based on al-Qur'an and al-Hadith according to the opinion of Muslim scholars.